Coral degradation impairs learning of non‐predators by Whitetail damselfish. (25th March 2021) - Chivers, Douglas P.; McCormick, Mark I.; Fakan, Eric P.; Edmiston, Jake W.; Ferrari, Maud C. O.
Abstract: A prerequisite for effective antipredator responses is the ability of a prey to distinguish animals that pose a threat from those that do not. Prey often have efficient learning mechanisms to learn threats but learning to recognize nonpredators may be equally or more important. Moreover, the ability to generalize learned information is of key importance for prey animals. Prey take information they know about one species to make 'educated guesses' about the predatory/nonpredatory status of other unknown species. Here, we investigate the ability of Whitetail damselfish Pomacentrus chrysurus to learn the identity of non‐predators and then generalize their responses to other unknown animals. Our work is completed within the context of unprecedented habitat degradation in reef ecosystems. When corals die, the remaining skeleton is colonized by algae, cyanobacteria and sessile invertebrates. These opportunistic colonists change the physical and chemical landscape of the reef and hence the background odour in which predator and non‐predator recognition occurs. Our results indicated that Whitetail damselfish learn to classify Moonwrasse Thalasomma lunare as a non‐predator through the process of latent inhibition, whereby the prey are repeatedly exposed to Moonwrasse odour multiple times in the absence of negative reinforcement. These fish subsequently generalized their nonpredator recognition to other unknown wrasse, but not distantly related fish. Of key importance was our finding that the patterns and extent of non‐predator learning and generalization were dramatically altered in dead coral habitats. As predicted, prey that learned the Moonwrasse as a nonpredator in live coral environments did not subsequently respond to Moonwrasse when we tried to teach them Moonwrasse was a predator in live coral. However, this non‐predator recognition was reduced in dead coral environments. Moreover, generalization completely failed when we changed from live to dead coral environments. Juvenile damselfishes need to rapidly catalogue the identity of unknown animals when they arrive at a reef. Changing background odours, that occur with changing tides and currents, means that prey need to learn non‐predator identities separately in each water source. This cognitive challenge likely has significant survival consequence in a changing environment. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.